A method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material

Through the mixed manganese source and segmented sintering process, combined with low-temperature annealing and additive doping, the problem of lithium manganate positive electrode material with high capacity attenuation and high preparation cost at high temperature is solved, and high capacity long life and excellent cycling performance are achieved. Industrialized production.

CN117776268BActive Publication Date: 2024-12-17TAIZHOU SHANNENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311821900.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2024-12-17
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

The existing lithium manganate positive electrode material has fast reversible capacity attenuation during charging and discharging at high temperatures, and the preparation process is high, the environmental protection is poor, the tap density is low, and the circulation performance is poor, which affects its commercial development.

Method used

Mixed manganese sources include trimanium tetraoxide, electrolytic manganese dioxide, manganese carbonate and manganese sulfate, and then mixed by ball milling and perform segmented sintering and low-temperature annealing. Add appropriate amount of additives such as niobium pentoxide to control the sintering temperature and time to increase the Cyclic stability and electrochemical properties of the material.

Benefits of technology

The preparation of high-capacity, long-life lithium manganate positive electrode material is achieved, which reduces manufacturing costs, improves the circulation and electrochemical properties of the material, is suitable for industrial production, and has a simple process and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117776268B_ABST
    Figure CN117776268B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of positive electrode materials for lithium-ion batteries, and provides a method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material. The preparation method comprises the following steps: mixing a lithium source, an additive and a mixed manganese source to obtain a lithium manganese oxide precursor, and subjecting the lithium manganese oxide precursor to a single sintering treatment to obtain a high-capacity and long-life lithium manganese oxide positive electrode material. The preparation method provided by the present invention does not require special crushing equipment and processes, reduces the manufacturing difficulty and processes, and greatly reduces the manufacturing cost of the lithium manganese oxide material. The prepared lithium manganese oxide positive electrode material has both high tap and compaction density and the advantages of high capacity and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a method for preparing a high-capacity and long-life lithium manganate positive electrode material. Background Art

[0002] Lithium manganese oxide has great advantages in the lithium-ion power supply market due to its low cost, environmental friendliness and abundant manganese resources. However, due to the defect of rapid reversible capacity decay during the charging and discharging process of lithium manganese oxide positive electrode materials at high temperatures, its commercial development is restricted. At present, it is generally believed that its capacity decay is caused by the following three reasons:

[0003] 1) Jahn-Teller effect: This effect causes Mn 3+ The lattice structure is distorted, causing an irreversible transformation from cubic to tetragonal, resulting in lattice collapse and ultimately a rapid decay of reversible capacity.

[0004] 2) Dissolution of manganese: Mn on the particle surface occurs 3+ Disproportionation reaction of 2Mn 3+ (s)→Mn 4+ (s)+Mn 2+ (l) At the same time, the decomposition of lithium salts such as LiPF6 in the electrolyte produces HF, which accelerates the dissolution of manganese, causing the loss of active substances, and finally leading to a decrease in discharge specific capacity and a decrease in cycle performance.

[0005] 3) Oxidative decomposition of electrolyte: Under high voltage, the oxidative decomposition of electrolyte will cause the surface of positive electrode material to form an inert substance SEI film, which will cover the surface of the material and hinder the Li + Diffusion increases the internal resistance and reduces the reversible capacity.

[0006] A Chinese patent with publication number CN103682315A reports a method for preparing a high-capacity, long-life lithium-ion battery lithium manganese oxide positive electrode material. The patent is a mixture of lithium carbonate, manganese sulfate, and additives, and ethanol is used as a ball milling dispersion solvent for wet ball milling. After the material is dried, the lithium manganese oxide material is obtained by two sinterings. The patent uses manganese sulfate as the manganese source and ethanol as a ball milling dispersant, which does not meet the current national environmental protection requirements and is not conducive to large-scale industrial production, and also increases the difficulty and cost of tail gas treatment. The patent uses ethanol as a ball milling dispersant and a wet ball milling process, which will increase the material drying link and invisibly increase the manufacturing cost; it is also necessary to improve the fire safety level of the patented production facility, which greatly increases the maintenance cost of the site. In addition, the lithium manganese oxide prepared by the patent also has the problem of low tap density and low first effect, which is easy to cause cracking of the coating slurry and the problem of low performance of the prepared battery, which seriously affects the use of lithium manganese oxide.

[0007] In addition, although the lithium manganate prepared by other existing technologies using manganese dioxide has a high vibration and compaction density, the raw material manganese dioxide contains a large amount of impurities, resulting in a low capacity of the product and poor cycle performance. The lithium manganate prepared by using manganese tetraoxide has a high purity, a high capacity of the prepared product and good cycle performance, but has a low vibration and compaction density, and is easy to harden after sintering, and adheres to the sagger, making it difficult to remove the sagger.

[0008] Therefore, how to provide a method for preparing a high-capacity, long-life lithium manganese oxide positive electrode material with low manufacturing cost, simple and feasible preparation process, cheap raw materials, safety and environmental protection has become a problem that technicians in this field need to solve urgently. Summary of the invention

[0009] In view of this, the present invention provides a method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material, which aims to solve the technical problems of low vibration and compaction density, low capacity, poor cycle performance, etc. existing in lithium batteries.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The present invention provides a method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material, comprising the following steps:

[0012] A lithium source, an additive and a mixed manganese source are mixed to obtain a lithium manganate precursor, and the lithium manganate precursor is subjected to a sintering treatment to obtain a high-capacity and long-life lithium manganate positive electrode material;

[0013] The mixed manganese source includes at least two of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate.

[0014] Furthermore, the molar ratio of the Mn element in the mixed manganese source to the Li element in the lithium source is 2:1.06-1.20.

[0015] Furthermore, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate.

[0016] Furthermore, the additive includes one or more of niobium pentoxide, aluminum oxide, magnesium oxide, magnesium carbonate, titanium dioxide, boric acid, lithium fluoride and aluminum fluoride; the mass of the additive is 0.1-5% of the total mass of the lithium source and the mixed manganese source.

[0017] Furthermore, the mixing is performed by ball milling, the ball milling speed is 200-400 rpm, the ball milling time is 2-4 hours, and the ball-to-material ratio is 1:1-4.

[0018] Furthermore, the particle size of the lithium manganate precursor is 6 to 12 μm.

[0019] Furthermore, the primary sintering process includes a first stage sintering, a second stage sintering and annealing performed sequentially.

[0020] Furthermore, the temperature of the first sintering stage is 450-650° C., and the time of the first sintering stage is 5-10 hours.

[0021] Furthermore, the temperature of the second-stage sintering is 650-850° C., and the time of the second-stage sintering is 10-20 hours.

[0022] Furthermore, the annealing temperature is 600-800° C., and the annealing time is 4-10 hours.

[0023] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] The present invention adopts mixed manganese source to prepare lithium manganate material. After high-temperature sintering, the material has a loose texture and can be directly screened and packaged without the need to purchase crushing equipment, which greatly saves the initial production capital investment.

[0025] The present invention firstly adopts dry mixing and segmented sintering to improve the cyclic stability and electrochemical performance of lithium manganate positive electrode materials. By means of ion co-doping, the product structure is improved, and the electrochemical gram capacity, compaction density, rate discharge performance and cycle performance of lithium manganate products are effectively improved. In addition, the production process is simple, the process is easy to control, the energy consumption is low, the efficiency is high, and the cost is low, which is suitable for industrial production.

[0026] The present invention adopts a low-temperature annealing process in the preparation process to compensate for the loss of oxygen ions in the lattice and improve the crystallinity of the material; and adopts additive-doped lithium manganate for mixed sintering to reduce Mn dissolution loss and improve the cycle life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM images of lithium manganate prepared in Example 1 at different magnifications;

[0028] Figure 2 The XRD diffraction pattern of lithium manganate prepared in Example 1;

[0029] Figure 3 The charge and discharge curve of the battery using lithium manganese oxide prepared in Example 1 as the positive electrode material;

[0030] Figure 4 This is a cycle stability diagram of a battery using lithium manganese oxide prepared in Example 1 as the positive electrode material;

[0031] Figure 5 This is a graph showing the capacity retention rate of a battery using lithium manganese oxide prepared in Example 1 as the positive electrode material. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material, comprising the following steps:

[0033] A lithium source, an additive and a mixed manganese source are mixed to obtain a lithium manganate precursor, and the lithium manganate precursor is subjected to a single sintering treatment to obtain a high-capacity and long-life lithium manganate positive electrode material.

[0034] In the present invention, the mixed manganese source comprises at least two of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate, preferably at least two of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate and manganese sulfate, and more preferably manganese tetraoxide and electrolytic manganese dioxide; the mass ratio of manganese tetraoxide to electrolytic manganese dioxide is preferably 1-9:1-9, more preferably 3-7:3-7, and even more preferably 4-6:4-6; the particle size of the manganese source is independently preferably D 50 =5 to 20 μm, more preferably D 50 =8 to 16 μm, more preferably D 50 =10~15μm.

[0035] In the present invention, the molar ratio of the Mn element in the mixed manganese source to the Li element in the lithium source is 2:1.06-1.20, preferably 2:1.08-1.18, and more preferably 2:1.10-1.15.

[0036] In the present invention, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate, preferably one or more of lithium carbonate, lithium hydroxide, lithium oxalate and lithium sulfate, and more preferably lithium carbonate or lithium hydroxide.

[0037] In the present invention, the additive includes one or more of niobium pentoxide, aluminum oxide, magnesium oxide, magnesium carbonate, titanium dioxide, boric acid, lithium fluoride and aluminum fluoride, preferably one or more of niobium pentoxide, aluminum oxide, titanium dioxide, boric acid, lithium fluoride and aluminum fluoride, and more preferably niobium pentoxide or boric acid; the mass of the additive is 0.1-5% of the total mass of the lithium source and the mixed manganese source, preferably 1-4%, and more preferably 2-3%.

[0038] In the present invention, the mixing is performed by ball milling, and the ball milling equipment is a planetary ball mill or an oblique ball mill, preferably a planetary ball mill; the ball milling speed is 200-400rpm, preferably 240-360rpm, and more preferably 260-340rpm; the ball milling time is 2-4h, preferably 2.5-3.5h, and more preferably 3.0h; the ball-to-material ratio is 1:1-4, preferably 1:1.5-3.5, and more preferably 1:2-3.

[0039] In the present invention, the particle size of the lithium manganate precursor is 6 to 12 μm, preferably 7 to 10 μm, and more preferably 8 to 9 μm.

[0040] In the present invention, the primary sintering process includes a first-stage sintering, a second-stage sintering and annealing performed in sequence, and the sintering atmospheres of the first-stage sintering and the second-stage sintering are both air.

[0041] In the present invention, the temperature of the first sintering stage is 450-650°C, preferably 480-620°C, more preferably 500-600°C; the time of the first sintering stage is 5-10h, preferably 6-9h, more preferably 7-8h.

[0042] In the present invention, the temperature of the second stage sintering is 650-850°C, preferably 680-820°C, and more preferably 700-800°C; the time of the second stage sintering is 10-20h, preferably 12-18h, and more preferably 14-16h.

[0043] In the present invention, the annealing temperature is 600-800° C., preferably 640-760° C., and more preferably 680-750° C.; the annealing time is 4-10 h, preferably 5-9 h, and more preferably 6-8 h.

[0044] In the present invention, the heating rate from room temperature to the temperature of the first sintering is 1 to 10°C / min, preferably 2 to 8°C / min, and more preferably 4 to 6°C / min; the heating rate from the temperature of the first sintering to the temperature of the second sintering is 1 to 10°C / min, preferably 2 to 8°C / min, and more preferably 4 to 6°C / min; the cooling rate from the temperature of the second sintering to the annealing temperature is 1 to 5°C / min, preferably 2 to 4°C / min, and more preferably 3°C / min.

[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] 297g of manganese tetraoxide, 780g of electrolytic manganese dioxide, 224g of lithium carbonate and 15g of niobium pentoxide were put into an oblique ball mill for ball milling and mixing. The ball mill speed was 290r / min, the ball-to-material ratio was 1:2, and the lithium manganate precursor with a particle size between 7 and 9μm was obtained by ball milling for 2h. The lithium manganate precursor was subjected to one-stage sintering, two-stage sintering and annealing treatment, wherein the heating rate during the first sintering was 5℃ / min, the sintering temperature was 570℃, and the second stage sintering was performed after 10h of heat preservation; the heating rate during the second stage sintering was 5℃ / min, the sintering temperature was 825℃, and the annealing was performed after 16h of heat preservation; the cooling rate during annealing was 3℃ / min, the annealing temperature was 700℃, and the heat preservation was 6h. Cool to room temperature, and directly sieve through a 200-mesh sieve to obtain spinel lithium manganate.

[0048] Example 2

[0049] 65 g of aluminum oxide was added during ball milling, and the remaining parameters and steps were the same as those in Example 1.

[0050] Example 3

[0051] 15 g of niobium pentoxide was replaced by 65 g of aluminum oxide, and the remaining parameters and steps were the same as those in Example 1.

[0052] Example 4

[0053] 15 g of niobium pentoxide was replaced by 65 g of titanium dioxide, and the remaining parameters and steps were the same as those in Example 1.

[0054] Example 5

[0055] The mass of lithium carbonate was adjusted to 235 g, and the remaining parameters and steps were the same as in Example 1.

[0056] Example 6

[0057] The mass of lithium carbonate was adjusted to 315 g, and the remaining parameters and steps were the same as in Example 1.

[0058] Example 7

[0059] The particle size of the lithium manganate precursor was adjusted to 10-11 μm, and the remaining parameters and steps were the same as those in Example 1.

[0060] Example 8

[0061] The temperature of the second stage sintering was adjusted to 815° C. and kept at this temperature for 14 h. The other parameters and steps were the same as those in Example 1.

[0062] Example 9

[0063] The temperature of the second stage sintering was adjusted to 835° C. and kept at this temperature for 14 h. The other parameters and steps were the same as those in Example 1.

[0064] Comparative Example 1

[0065] The amount of niobium pentoxide was adjusted to 1 g, and the other parameters and steps were the same as those in Example 1.

[0066] Comparative Example 2

[0067] The amount of niobium pentoxide was adjusted to 78 g, and the remaining parameters and steps were the same as those in Example 1.

[0068] Comparative Example 3

[0069] 1156 g of electrolytic manganese dioxide was used alone as the manganese source, and the remaining parameters and steps were the same as those in Example 1.

[0070] Comparative Example 4

[0071] 963 g of trimanganese tetraoxide was used alone as the manganese source, and the remaining parameters and steps were the same as those in Example 1.

[0072] Comparative Example 5

[0073] The annealing step was deleted, and the remaining parameters and steps were the same as those in Example 1.

[0074] The physical properties of the lithium manganese oxide prepared in Example 1 were analyzed, and the physical properties are shown in Table 1.

[0075] Table 1 Physical properties of lithium manganate prepared in Example 1

[0076]

[0077] The physical properties of the lithium manganate prepared in Examples 1 to 9 and Comparative Examples 1 to 5 are shown in Table 2.

[0078] Table 2 Physical properties of lithium manganate prepared in Examples and Comparative Examples

[0079] No. pH <![CDATA[BET(m 2 / g)]]> <![CDATA[Tap density (g / cm 3 )]]> <![CDATA[D 10 μm]]> <![CDATA[D 50 μm]]> <![CDATA[D 90 μm]]> Example 1 8.35 0.72 1.96 5.73 15.45 30.82 Example 2 8.97 0.73 1.92 12.33 26.19 47.13 Example 3 8.91 1.03 1.85 3.59 11.65 26.17 Example 4 8.98 1.02 1.82 3.86 11.65 26.06 Example 5 8.49 0.73 1.66 7.40 17.56 34.21 Example 6 7.38 0.71 1.53 5.88 15.40 29.66 Example 7 7.52 0.68 1.74 6.43 16.40 31.97 Example 8 6.82 0.51 1.71 6.52 16.69 32.72 Example 9 7.40 0.67 1.64 7.19 17.15 32.41 Comparative Example 1 8.13 0.73 1.91 5.80 15.37 30.59 Comparative Example 2 6.82 0.75 2.12 5.44 15.09 30.25 Comparative Example 3 7.68 0.76 1.65 5.44 14.78 29.54 Comparative Example 4 8.77 0.55 1.65 7.79 18.37 37.78 Comparative Example 5 9.12 0.82 1.76 6.15 15.69 30.04

[0080] Electrochemical performance test: Lithium manganate, acetylene black and PVDF were mixed in a mass ratio of 8:1:1 and dissolved in NMP to form a positive electrode slurry with a solid content of 70%, then coated on aluminum foil and placed in a vacuum drying oven at 120°C for 3 hours. A CR2025 button battery was prepared with a metal lithium sheet as the negative electrode and 1 mol / L LiPF6 as the electrolyte. The electrochemical test voltage range was 3.0 to 4.3V, and after 5 cycles of 0.5C (1C = 110mAh / g), 100 cycles of 1C were performed. The test results are shown in Table 3; the LMO battery prepared by Polyfluoro Chemical Co., Ltd. and the LMO battery prepared by Guangxi Lijin New Materials Co., Ltd. were also subjected to the same electrochemical test, and the performance of the button battery made of lithium manganate prepared in Example 1 of the present invention was compared. The results are shown in Table 3. Figures 4-5. (NMP: N-methyl-2-pyrrolidone; PVDF: polytetrafluoroethylene).

[0081] Table 3 Electrochemical properties of lithium manganate prepared in Examples and Comparative Examples

[0082]

[0083] manual

[0084]

[0085] Compared with Examples 2 to 4, Example 1 shows that by doping a small amount of niobium pentoxide into the lithium manganate structure, the +5-valent niobium can effectively reduce the average valence of Mn in the material and increase the Mn content in the material. 3+ The amount of can increase the discharge capacity of lithium manganese oxide and reduce the pH value of lithium manganese oxide.

[0086] Compared with Examples 5 to 6, Example 1 has different Li / Mn ratios in the materials, resulting in different cycle stability of the samples after sintering. The stability of the sample with a lower Li content is poor after sintering; the pH of the sample with a higher Li content is higher after sintering, and the performance is not significantly improved, resulting in a waste of Li. Therefore, the Li / Mn ratio of the lithium manganate material is 1.08 / 2, which has the best effect.

[0087] Compared with Example 7, Example 1 has a smaller particle size of the precursor, resulting in more oversize material, resulting in a lower actual yield and lower output, so the best effect is achieved when the precursor ball milling particle size is 8 to 9 um.

[0088] Compared with Examples 8-9, Example 1 adjusts the staged sintering temperature of the lithium manganate material; when the temperature of the second stage sintering is 815°C and the holding time is 14h. The lower sintering temperature causes the material to react incompletely, the sample has a larger tap density and a higher pH. When the temperature of the second stage sintering is 835°C and the holding time is 14h, the sintering temperature increases, causing Li to volatilize at high temperature and the material performance to decrease.

[0089] In Example 1, compared with Comparative Examples 1 to 2, the doping ratio of niobium is increased, resulting in a decrease in the pH value of the material to be weakly acidic; when the doping ratio is reduced, the pH value increases to be strongly alkaline, which is not conducive to the subsequent use of the material, and the performance of the sample is poor. The best effect is achieved when the doping ratio of niobium pentoxide is 0.8%.

[0090] Compared with Comparative Example 3, Example 1 uses electrolytic manganese dioxide as the Mn source to prepare lithium manganate. The tap density of the product is larger, but its first capacity is lower, the first efficiency is poor, and the 1C cycle performance is poor.

[0091] Compared with Comparative Example 4, Example 1 uses manganese tetraoxide as the Mn source to prepare lithium manganate. The tap density of the product is small, the sample shrinks and hardens into a hard block that is difficult to separate from the sagger, and needs to be ball-milled before it can pass through a 200-mesh sieve. The sample has a lower initial capacity, but better initial efficiency and cycle stability.

[0092] Compared with Example 5, Example 1 does not use the low-temperature annealing process, and the pH of the sample is higher. Its first capacity and first efficiency are worse than those of Example 2, and the capacity retention rate is significantly reduced.

[0093] Figure 1 This is the SEM image of the sample in Example 1. From the photo, it can be seen that the prepared sample uses a mixed manganese source, the particle size is uniform, and there is no obvious agglomeration phenomenon. From the enlarged SEM image, it can be seen that the prepared lithium manganese oxide grains are spherical rather than the octahedral crystal form of common lithium manganese oxide, which greatly reduces the dissolution loss caused by the Jahn-Teller effect of the example sample and improves the service life of the material.

[0094] Figure 2 This is the XRD diffraction pattern of the sample in Example 1. All diffraction peaks of the sample are consistent with the PDF card data, proving that appropriate doping with niobium pentoxide has no effect on the crystal structure of lithium manganate.

[0095] Figure 3 The charge and discharge curve of the sample in Example 1 is shown in FIG. Figure 3 It can be seen that the 0.5C initial charge specific capacity of the lithium manganese oxide positive electrode material prepared in Example 1 is 131.2 mAh / g, and the discharge specific capacity is 129.82 mAh / g.

[0096] Figures 4-5 The cycle and capacity retention rate curve of the sample in Example 1 is shown in FIG. Figures 4-5 It can be seen that the 1C, 100-cycle discharge specific capacity of the lithium manganese oxide positive electrode material prepared in Example 1 is 123.8 mAh / g, the cycle performance is relatively stable, and the capacity retention rate is 96.87%; under the same conditions as the power-off test conditions of the present invention, samples from other manufacturers all experience drastic capacity decay in the later stage of the test.

[0097] The above shows that the lithium manganese oxide positive electrode material prepared by the present invention has a narrow particle size distribution, a small BET, a good tap density, and a correspondingly high volume energy density; the prepared lithium ion battery has excellent first efficiency and capacity retention rate, and effectively improves the cycle performance of the lithium ion battery. In addition, the preparation method can obtain a spinel lithium manganese oxide positive electrode material with excellent cycle stability under the condition of shortening the calcination time.

[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-capacity and long-life lithium manganese oxide positive electrode material, characterized in that: The following steps are involved: A lithium source, an additive and a mixed manganese source are mixed to obtain a lithium manganate precursor, and the lithium manganate precursor is subjected to a sintering treatment to obtain a high-capacity and long-life lithium manganate positive electrode material; The mixed manganese source includes at least two of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate; The additive comprises one or more of niobium pentoxide, magnesium oxide, magnesium carbonate, titanium dioxide, boric acid and lithium fluoride; the mass of the additive is 0.1-5% of the total mass of the lithium source and the mixed manganese source; The mixing is carried out by ball milling, the ball milling speed is 200-400 rpm, the ball milling time is 2-4 hours, and the ball-to-material ratio is 1:1-4; The particle size of the lithium manganate precursor is 6 to 12 μm; The primary sintering process includes a first-stage sintering, a second-stage sintering and annealing performed sequentially.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the Mn element in the mixed manganese source to the Li element in the lithium source is 2:1.06-1.

20.

3. The preparation method according to claim 2, characterized in that: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate.

4. The preparation method according to claim 3, characterized in that: The temperature of the first stage sintering is 450-650° C., and the time of the first stage sintering is 5-10 hours.

5. The preparation method according to claim 1 or 4, characterized in that: The temperature of the second stage sintering is 650-850° C., and the time of the second stage sintering is 10-20 hours.

6. The preparation method according to claim 5, characterized in that: The annealing temperature is 600-800° C., and the annealing time is 4-10 hours.